Project scope management : a practical guide to requirements for engineering, product, construction, IT and enterprise projects - Moustafaev, Jamal, 1973- (Best practices and advances in program management series., 2015)
Incomplete or missed requirements, omissions, ambiguous product features, lack of user involvement, unrealistic customer expectations, and the proverbial scope creep can result in cost overruns, missed deadlines, poor product quality, and can very well ruin a project. Project Scope Management: A Practical Guide to Requirements for Engineering, Product, Construction, IT and Enterprise Projects describes how to elicit, document, and manage requirements to control project scope creep. It also explains how to manage project stakeholders to minimize the risk of an ever-growing list of user requirements. The book begins by discussing how to collect project requirements and define the project scope. Next, it considers the creation of work breakdown structures and examines the verification and control of the scope. Most of the book is dedicated to explaining how to collect requirements and how to define product and project scope inasmuch as they represent the bulk of the project scope management work undertaken on any project regardless of the industry or the nature of the work involved. The book maintains a focus on practical and sensible tools and techniques rather than academic theories. It examines five different projects and traces their development from a project scope management perspective--from project initiation to the end of the execution and control phases. The types of projects considered include CRM system implementation, mobile number portability, port upgrade, energy-efficient house design, and airport check-in kiosk software. After reading this book, you will learn how to create project charters, high-level scope, detailed requirements specifications, requirements management plans, traceability matrices, and a work breakdown structure for the projects covered.